Proceedings of the 3rd Green Development International Conference (GDIC 2020) 2021
DOI: 10.2991/aer.k.210825.039
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Information Technology in Improving the Quality of Financial Report in Micro, Small and Medium Enterprises

Abstract: Micro, small and medium enterprises have an important role in the economy of a country. Although the role of micro, small and medium enterprises has been recognized nationally, these enterprises face many challenges and obstacles, especially in producing quality financial report. For this reason, this study was conducted to investigate the use of information technology in improving the quality of financial report for micro, small and medium enterprises. To achieve this goal, this study developed a structural q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…For digital transformation, previous studies found that the quality of accounting information is affected by digital transformation (Johnston & Zhang, 2018;Gulin, Hladika, & Valenta, 2019;Wiralestari, Rita, & Riski 2020;Phornlaphatrachakorn & Kalasindhu, 2021;Hasan, 2023). For example, Hasan (2023) found that the more a company moves towards digital transformation the more it leads to adequacy and reliability of accounting information and thus benefits its users.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For digital transformation, previous studies found that the quality of accounting information is affected by digital transformation (Johnston & Zhang, 2018;Gulin, Hladika, & Valenta, 2019;Wiralestari, Rita, & Riski 2020;Phornlaphatrachakorn & Kalasindhu, 2021;Hasan, 2023). For example, Hasan (2023) found that the more a company moves towards digital transformation the more it leads to adequacy and reliability of accounting information and thus benefits its users.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the reasons for using digital technologies is to improve the communication between preparers and users of financial reports. From this perspective, digitalization is a valuable approach to help organizations provide high-quality financial reports, providing useful, accuracy, and timely accounting information for effective decision-making (Wiralestari et al, 2020). This research contributes to the literature on the timing of financial reporting in two ways.…”
Section: Introductionmentioning
confidence: 98%
“…Profitability is defined as the ability of a company to generate profits from its sources, such as assets, capital, or business income. According to Wiralestari ( 2021) , decision making is influenced by information from financial reports and the financial reports themselves. Profit margin is a measure used to determine how well a business generates profits.…”
Section: Introductionmentioning
confidence: 99%